An integrative taxonomic approach to characterize Trichogramma marandobai (Hymenoptera: Trichogrammatidae) - Vieira, Jaci Mendes; Querino, Ranyse B.; Cônsoli, Fernando L.; Zucchi, Roberto A. (Zootaxa, 2015)
Trichogramma is the largest genus of Trichogrammatidae, with nearly 210 species worldwide (Pinto 2006), of which 41 species occur in South America and 26 in Brazil (Zucchi et al. 2010). Trichogramma are tiny parasitoids of eggs of insects, mostly lepidopterans. Some species have been mass-reared for biological control of agricultural pests.